MicroRNA regulation in an animal model of acute ocular hypertension - Wang, Jiawei; Valiente-Soriano, Francisco J.; Jonas, Jost B. (Acta ophthalmologica, 2017)
Purpose To analyse miRNA regulation in a rat model of acute ocular hypertension (AOH). Methods Acute ocular hypertension (AOH) was induced in the left eye of adult albino rats by inserting a cannula connected with a saline container into the anterior chamber. The contralateral eye served as a control. Seven days later, animals were killed. Retinas were used either for quantitative analysis of retinal ganglion cells (RGCs) and microglial cells or for miRNA array hybridization, qRT-PCR and Western blotting. Results Anatomically, AOH caused axonal degeneration, a significant loss of RGCs and a significant increase in microglial cells in the ganglion cell layer. The miRNAs microarray analysis revealed 31 differentially expressed miRNAs in the AOH versus control group, and the regulation of 12 selected microRNAs was further confirmed by qRT-PCR. Bioinformatic analysis indicates that several signalling pathways are putatively regulated by the validated miRNAs. Of particular interest was the inflammatory pathway signalled by mitogen-activated protein kinases (MAPKs). In agreement with the in silico analysis, p38 MAP kinase, tumour necrosis factor-alpha (TNF-α) and iNOS proteins were significantly upregulated in the AOH retinas. Conclusions Acute IOP elevation led to changes in the expression of miRNAs, whose target genes were associated with the regulation of microglia-mediated neuroinflammation or neural apoptosis. Addressing miRNAs in the process of retinal ischaemia and optic nerve damage in association with high IOP elevation may open new avenues in preventing retinal ganglion cell apoptosis and may serve as target for future therapeutic regimen in acute ocular hypertension and retinal ischaemic conditions.